Al-‘Afālu al-Kalāmiyatu al-Taujihiyyatu fī al-Rusūmi al-Mutaharrikati “al-Riḥlatu” (Dirāsatu tahlīliyatu tadāwuliyatu) - Sukmawati, Amalia; Yusuf, Mohammad; Khasanah, Mushokhikhul (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
Directive speech act is an utterance performed by a speaker which has the function of making the other person act as what is said. One of the directive speech acts was found in the animation "Ar-Rihlah". in the animation "Ar-Rihlah". The purpose of this study is to describe the types and functions of directive speech acts in the animation "Ar-Rihlah". In this thesis the author discusses directive speech acts in the animation "Ar-Rihlah". The aims of this study are: 1) To find out the types of directive speech acts in the animation "Ar-Rihlah." 2) To find out the function of directive speech acts in the animation. As for this research is library research. This study uses a descriptive method with a qualitative approach, and the data source for this research is the speech acts in the animation "Ar-Rihlah." Researchers used in-depth observation techniques. Using this method, it can be concluded that the results of this study: 1) The types of directive speech acts in the animation "Ar-Rihlah" are direct directive speech acts and indirect directive speech acts. 2) There are six types of directive speech acts in the animation "Ar-Rihlah" namely requestives, quoestions, requirements, prohibitives, permissives, advisories. The results of research on directive speech acts in the animation "Ar-Rihlah" show that the form of directive speech acts that is most often uttered is the question type of speech act, which amounts to 17 data. Requestives which functions to request 3 data, pray 1 data, request 1 data, invite 4 data. Questions that function to ask as many as 15 data, integrate 2 data. Requirements which function to order as many as 7 data, probobitives which function to prohibit as many as 3 data. Permissives function to approve as much as 2 data. Advisories which function to advise as many as 5 data, warn as many as 4 data.